Take control of your health - Mercola, Joseph
Take Control of Your Health was written with you in mind -- a concerned individual who wants to improve your health and live better, but is confused by the mountains of conflicting information out on the web. Many people just can't sort through it all. "Should I go no-carb or low-carb?" "Is aerobic exercise really the best way to burn fat?" "Are prescription drugs really safe, or are there alternatives?" "Does the government really have my best interests at heart?" "Are there fats that are actually good for you?" Take Control of Your Health cuts through all the deceptions and half-truths and gives it to you straight. Listen, even my website has over 50,000 pages of content with more coming in all the time.